2015
DOI: 10.1016/j.pharmthera.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

EGFR targeted therapies and radiation: Optimizing efficacy by appropriate drug scheduling and patient selection

Abstract: The epidermal growth factor receptor (EGFR) plays an important role in tumor progression and treatment resistance for many types of malignancies including head and neck, colorectal, and nonsmall cell lung cancer. Several EGFR targeted therapies are efficacious as single agents or in combination with chemotherapy. Given the toxicity associated with chemoradiation and poor outcomes seen in several types of cancers, combinations of EGFR targeted agents with or without chemotherapy have been tested in patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 143 publications
2
37
0
Order By: Relevance
“…Besides, we also detected the detailed mechanisms for inhibiting effect of EGFR‐TKIs on DNA damage repair. The results of our data showed that combined AZD3759 with radiation significantly prolonged the presence of DNA DSBs compared to radiation alone, this is in line with previous studies . Moreover, the results of western blot and co‐IP showed that in response to radiation, there was radiation dose‐dependently decrease in rad51 expression and dose‐dependently increase in binding between DNA‐PKcs and EGFR in nucleus.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, we also detected the detailed mechanisms for inhibiting effect of EGFR‐TKIs on DNA damage repair. The results of our data showed that combined AZD3759 with radiation significantly prolonged the presence of DNA DSBs compared to radiation alone, this is in line with previous studies . Moreover, the results of western blot and co‐IP showed that in response to radiation, there was radiation dose‐dependently decrease in rad51 expression and dose‐dependently increase in binding between DNA‐PKcs and EGFR in nucleus.…”
Section: Discussionsupporting
confidence: 91%
“…Altered EGFR signaling is widely implicated in cell apoptosis resistance, proliferation, radiotherapy resistance, metastasis and invasion [16, 17]. Targeted therapies for treatment of NPC have become a topic of increased research interest internationally due to favorable efficacy and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the combination of EGFR blockade and radiation exploits three distinct roles that the EGFR pathway plays in cancer progression: enhanced cell proliferation, the activation of pro-survival pathways, and DNA repair [8]. What follows is a brief explanation of these functions and of the mechanisms of resistance to anti-EGFR therapies.…”
Section: Molecular Mechanisms Of Egfr Blockade Plus Radiation and Resmentioning
confidence: 99%
“…Radiation promotes the internalization and transport of EGFR by caveolin-1, leading to the activation of DNA-PK (a vital kinase for joining repair) in response to DNA damage. In this respect, researchers have shown that inhibition of EGFR with cetuximab attenuates EGFR nuclear import and suppresses DNA-PK activity [8].…”
Section: Dna Repairmentioning
confidence: 99%